2011
DOI: 10.1021/ic201278a
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Interactions Through π–π Stacking in the Lamellar Compound [{Cu(bipy)(en)}{Cu(bipy)(H2O)}{VO3}4]n

Abstract: Structural, magnetic, and powder and single-crystal electron paramagnetic resonance (EPR) studies were performed on [{Cu(bipy)(en)}{Cu(bipy)(H(2)O)}{VO(3)}(4)](n) (bipy = 2,2'-bipyridine, en = ethylenediamine), which is a new copper-vanadium hybrid organic-inorganic compound containing Cu(II) and V(V) centers. The oxovanadium units provide an anionic scaffolding to the structure, where two types of Cu(II) coordination modes, octahedral (Cu1) and square pyramidal (Cu2), contribute to the magnetic properties. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…The work of Venegas et al assigned to a similar coupling of bipyridine molecules in lamellar [Cu(bipy)(en)Cu(bipy)(H 2 O)VO 34 ] n a coupling more than one order of magnitude smaller than in CuBMB. 87 Thus, we conclude that our results indicate that the largest exchange couplings in CuBMB are between Cu 1 and Cu 3 ions, related by inversion operations at distances of B6.5 Å. The DFT calculation confirms these experimental results with J c 3a,b 4 J c 2,4 .…”
Section: Intermolecular Superexchange Couplingssupporting
confidence: 85%
“…The work of Venegas et al assigned to a similar coupling of bipyridine molecules in lamellar [Cu(bipy)(en)Cu(bipy)(H 2 O)VO 34 ] n a coupling more than one order of magnitude smaller than in CuBMB. 87 Thus, we conclude that our results indicate that the largest exchange couplings in CuBMB are between Cu 1 and Cu 3 ions, related by inversion operations at distances of B6.5 Å. The DFT calculation confirms these experimental results with J c 3a,b 4 J c 2,4 .…”
Section: Intermolecular Superexchange Couplingssupporting
confidence: 85%
“…It has been previously reported that π-π interactions can give rise to long-range ferromagnetic ordering between metal ions. 17,22,23 Therefore we propose that these inter-molecular interactions may serve as adequate superexchange mediators between the di-copper(II) centres and account for the observed ferromagnetic exchange.…”
Section: Dalton Transactionsmentioning
confidence: 87%
“…A number of systems have been reported in which π-π stacking interactions play a major role in propagating the magnetic properties, eventually leading to long range magnetic ordering. [17][18][19][20] Some of the factors that play crucial roles in transmitting strong magnetic coupling are the distance between metal centres, the nature of the bridging ligands and the spin ground state. Recently, non-covalent interactions have been exploited in the design of polymetallic magnetic materials where supramolecular interactions bring enhanced magnetic ordering in the system.…”
mentioning
confidence: 99%
“…The bond lengths of V-O range from 1.598(3) to 1.828(3) Å and the O-V-O angles range from 106.42(10)°to 112.07(15)°(Table S1a †), which are consistent with previously reported vanadates. [19][20][21] As shown in Fig. 3 chains in the [100] direction.…”
Section: Ir Spectramentioning
confidence: 99%